Policy Challenges in the Fight against Childhood Obesity: Low Adherence in San Diego Area Schools to the California Education Code Regulating Physical Education - G. Consiglieri; L. Leon-Chi; R. S. Newfield (Journal of Obesity)
Objective. Assess the adherence to the Physical Education (PE) requirements per California Education Code in San Diego area schools. Methods. Surveys were administered anonymously to children and adolescents capable of physical activity, visiting a specialty clinic at Rady Children's Hospital San Diego. The main questions asked were their gender, grade, PE classes per week, and time spent doing PE. Results. 324 surveys were filled, with 36 charter-school students not having to abide by state code excluded. We report on 288 students (59% females), mostly Hispanic (43%) or Caucasian (34%). In grades 1–6, 66.7% reported under the 200 min per 10 school days required by the PE code. Only 20.7% had daily PE. Average PE days/week was 2.6. In grades 7–12, 42.2% had reported under the 400 min per 10 school days required. Daily PE was noted in 47.8%. Average PE days/week was 3.4. Almost 17% had no PE, more so in the final two grades of high school (45.7%). Conclusions. There is low adherence to the California Physical Education mandate in the San Diego area, contributing to poor fitness and obesity. Lack of adequate PE is most evident in grades 1–6 and grades 11-12. Better resources, awareness, and enforcement are crucial.